Indicators for mapping and assessment of ecosystem condition and of the ecosystem service habitat maintenance in support of the EU Biodiversity Strategy to 2020 - N. Votsi; D. Palaskas; D. Malak; Chatziiordanou, E.; Fitoka, E.; Chadjicharalambous, E. (2019)
A systematic approach to map and assess the “maintenance of nursery populations and habitats” ecosystem service (ES) (hereinafter called “habitat maintenance”) has not yet emerged. In this article, we present an ecosystem service framework implementation at landscape level, by proposing an approach for calculating and combining a series of indicators with spatial modelling techniques. Necessary conceptual elements for this approach are: a) ecosystem condition, b) supply and demand of the targeted ecosystem service and c) spatial relationships between the Service Providing Units (SPU) and the Service Connecting Units (SCU). Ecosystem condition is quantified and mapped based on two indicators, the Biodiversity State and the Anthropogenic Impact. Quantification and mapping of supply and demand are based on the hypothesis that high supply can be activated in strictly protected areas and that a demand is localised in the Natura 2000 sites (N2K), considering them as the Service Benefit Areas (SBA). Wetlands are assessed as SCU between the SBA and the landscape areas where the habitat maintenance ES is supplied. By assessing wetlands as SCU, we intent to highlight their role as biodiversity stepping stones and as green infrastructures. Overall, we conclude that the EU biodiversity policy demand for no net loss and for a coherent N2K network can be met by enhancing the delivery of the habitat maintenance ES. This approach can assist policy-makers in prioritisation of conservation and restoration targets, in line with the EU biodiversity strategy to 2020 and the preparation of the post-2020 Strategy. One Ecosystem 4: e32704. https://doi.org/10.3897/oneeco.4.e32704